Appendicular bilharzioma: An unusual cause of acute intestinal obstruction in childhood (a case report at Charles de Gaulle Paediatric Teaching Hospital of Ouagadougou) - Albert Wandaogo; Isso Ouédraogo; Toussaint Wendlamita Tapsoba; Emile Bandré; Francis Somkieta Ouédraogo; Bernadette Béré; Balima Elie (Wolters Kluwer Medknow Publications, 2016)
The authors report the case of a 12-year-old boy admitted to the surgical emergency department of Charles de Gaulle Paediatric Teaching Hospital of Ouagadougou for acute abdominal pain. A strangulation of the terminal ileum by a tumour-like appendix wound around the bowel loop was seen during operation. The histological examination of the removed appendix disclosed eggs of Schistosoma haematobium and concluded to bilharzian appendicitis. A course of praziquantel treatment was instituted, and the patient underwent an event-free recovery. Such cases report are infrequent, even in areas where bilharzia-related diseases are endemic. It is important to recognise them and to treat them in an aetiological manner so as to prevent any potential complications. The diagnosis is always an operatory and histological curiosity. Appendectomy and treatment with a course of praziquantel seem quite suitable for this situation.